Cyberbranding Interactivity in Micro, Small, and Medium Enterprises (MSMEs) of Asbhoel Distro - Senjani, Sena; Fardiah, Dedeh; Ratnasari, Anne (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2025)
Ashboel Distro entered the fashion industry by branding the use of professional soccer players. The branding is very tantalizing and quite a novelty for the development of the fashion industry in the digital era. The purpose is to analyzing the packaging of Distro Asbhoel cyberbranding content by using professional soccer players on Instagram. Method: Qualitative with a case study approach and inductive data analysis techniques. Results and conclusions: Asbhoel succeeded in building strong cyberbranding through interactive content packaging, dialogic communication, and consistent management of audience participation on Instagram. The strategy of using professional soccer players also proved effective in increasing brand awareness and building emotional connections with audiences. Implications: Reinforces the concepts of cyberbranding by demonstrating the importance of emotional engagement and two-way dialog in shaping brand loyalty. Provides guidance for businesses to design content, select the right influencers, and utilize audience feedback to build strong and sustainable branding.